2017
DOI: 10.1103/physrevlett.119.073002
|View full text |Cite
|
Sign up to set email alerts
|

Equilibration Dynamics of Strongly Interacting Bosons in 2D Lattices with Disorder

Abstract: Motivated by recent optical lattice experiments [J.-y. Choi et al., Science 352, 1547], we study the dynamics of strongly interacting bosons in the presence of disorder in two dimensions. We show that Gutzwiller mean-field theory (GMFT) captures the main experimental observations, which are a result of the competition between disorder and interactions. Our findings highlight the difficulty in distinguishing glassy dynamics, which can be captured by GMFT, and many-body localization, which cannot be captured by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…Interestingly enough, we observed that further increase of disorder makes the DW-type configurations tend to dynamically survive again. Recently, certain related experiment was performed on the ultra-cold atoms and similar result was obtained, i.e., the random chemical potential enhances life time of the high-energy configurations [44,50]. This may be an expected result, i.e., disorder enhances the localization.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly enough, we observed that further increase of disorder makes the DW-type configurations tend to dynamically survive again. Recently, certain related experiment was performed on the ultra-cold atoms and similar result was obtained, i.e., the random chemical potential enhances life time of the high-energy configurations [44,50]. This may be an expected result, i.e., disorder enhances the localization.…”
Section: Discussionmentioning
confidence: 52%
“…To study the real time evolution in the 2D system, we employ the time-dependent Gutzwiller method. This method is based on the mean-field approximation and is often used to explain the qualitative understanding of the experimental observations except for the 1D problems [27,[33][34][35]. Some studies have also used this method to study the quench dynamics relevant to the KZM [17,19,21,36].…”
Section: Time-dependent Gutzwiller Analysis Of Quench Dynamicsmentioning
confidence: 99%
“…It has been very successful at calculating both the static and dynamic properties of bosons in optical lattices, including slow transport in the presence of disorder [22,23]. Though a mean field theory is unable to capture some of the features of MBL, such as the growth of entanglement entropy or the behavior of individual energy eigenstates, it has been used to model similar experiments to the one we are considering here [9,24]. Ultimately, the agreement between our results and the experiment [8] shows that we have included the relevant physics in our modeling.…”
Section: Introductionmentioning
confidence: 99%